A case study of winter storm-induced continental shelf waves in the northern South China Sea in winter 2009. (15th August 2016) - Li, Junyi; Zheng, Quanan; Hu, Jianyu; Xie, Lingling; Zhu, Jia; Fan, Zhenhua
Abstract: This study deals with winter storm-induced continental shelf waves (CSWs) in the northern South China Sea in winter 2009 using tidal gauge data and along-track satellite altimeter data. The results show that the periods of CSWs propagating along the coast from Kanmen to Shuidong are in bands of 62 and 133 h. The phase speeds are in a range from 8 to 13 m s −1 between Kanmen and Shantou, from 9 to 11 m s −1 between Shantou and Huizhou and from 10 to 15 m s −1 between Huizhou and Shuidong, respectively. Satellite altimeter captured along-track sea level anomaly during the CSW events. Further analysis using the theoretical cross-shore CSW modes to fit the along-track sea level anomaly data indicates that the first three wave modes play important roles during the CSW events and the first mode is a dominant component. Highlights: We use ensemble empirical mode decomposition to decompose de-tided sea level data. Free continental shelf waves were generated by the winter storms. We use the theoretical cross-shore CSW modes to fit the along-track SLA data. The first three wave modes play important role during the CSW events.